Unlocking the secrets of doxepin hydrochloride's crystal structure: Insights from high-quality powder diffraction analysis - Dezena, Renan Marcel Bonilha; Rosa, Paulo César Pires (Annales pharmaceutiques françaises, 2024)
Doxepin hydrochloride, a versatile pharmaceutical compound, has been the subject of extensive research aimed at elucidating its crystal structure and solid-state characteristics. In this manuscript, we explore the significance of high-quality powder diffraction data in unveiling the intricate details of doxepin hydrochloride's crystal lattice. By examining the refined atom coordinates, density functional theory (DFT) optimization, and intermolecular interactions, we gain valuable insights into its structural conformation. This knowledge highlights the importance of precise crystallographic data in advancing our understanding of complex compounds and their pharmaceutical applications.